THE DOMESTIC STOCK MARKET REQUIRES CHANGE - P. Akinin; V. Akinina; R. Bolatchieva (Вестник Северо-Кавказского федерального университета)
The article presents an analysis of the domestic stock market: its dynamics, structure, deformation. In particular, it is noted that the dynamics is observed mainly in secondary positions. It is mainly characterized by stagnation and even a fall in the equity market sector. There are serious imbalances that reflect monopoly processes (in service, in industry and regional cuts). The authors proposed a structural-logical model of the role and place of the stock market and exchange trading in models and mechanisms of financial and economic development, which allows to take into account all the features and interrelations in the development of strategies, development programs of industries, regions, corporations, and in the preparation of educational materials financial literacy).